2015
DOI: 10.1038/ki.2015.159
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil serine proteases exert proteolytic activity on endothelial cells

Abstract: Neutrophil serine proteases (NSPs) are released from activated neutrophils during inflammation. Here we studied the transfer of the three major NSPs, namely proteinase 3, human neutrophil elastase, and cathepsin G, from neutrophils to endothelial cells and used an unbiased approach to identify novel endothelial NSP substrates. Enzymatically active NSPs were released from stimulated neutrophils and internalized by endothelial cells in a dose- and time-dependent manner as shown by immunoblotting, flow cytometry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 48 publications
(57 reference statements)
2
59
0
Order By: Relevance
“…Likewise, cleavage of annexin 1 by PR3 in the context of neutrophil activation reduces the anti-inflammatory activity of annexin 1 and points to a proinflammatory role of PR3. Transfer of PR3 into the cytosol of endothelial cells during neutrophil-endothelial cell interactions has also been inferred as a trigger of endothelial cell apoptosis, which appears to contribute to small vessel damage at sites of inflammation (Pendergraft et al, 2004;Jerke et al, 2015).…”
Section: Proteinase 3-targeting Inhibitors and Antibodies As Theramentioning
confidence: 99%
See 4 more Smart Citations
“…Likewise, cleavage of annexin 1 by PR3 in the context of neutrophil activation reduces the anti-inflammatory activity of annexin 1 and points to a proinflammatory role of PR3. Transfer of PR3 into the cytosol of endothelial cells during neutrophil-endothelial cell interactions has also been inferred as a trigger of endothelial cell apoptosis, which appears to contribute to small vessel damage at sites of inflammation (Pendergraft et al, 2004;Jerke et al, 2015).…”
Section: Proteinase 3-targeting Inhibitors and Antibodies As Theramentioning
confidence: 99%
“…Identification of PR3 as the third elastase-like protease Baggiolini et al, 1978Baggiolini et al, 1988 Elastolytic activity of PR3 showed in vivo Kao et al, 1988Kao et al, 1989 Role of PR3 in cell differentiation attributed Bories et al, 1989Bories et al, 1990 First synthetic inhibitors of PR3 reported Groutas et al, 1990 cDNA cloning of PR3 performed Campanelli et al, 1990 PR3 identified as the target antigen for C-ANCA Jenne et al, 1990 PR3 detected on the neutrophil cell surface Csernok et al, 1990Csernok et al, 1991 First biochemical and enzymatic characterization of PR3 performed Rao et al, 1991 Inhibition of PR3 by elafin investigated Wiedow et al, 1991Wiedow et al, 1992 Gene mapping of PR3 performed Sturrock et al, 1992 Substrate binding site of PR3 mapped using synthetic substrates and inhibitors Brubaker et al Kam et al, 1992aKam et al, ,b 1993 PR3 gene (PRTN3) localized on 19p13.3 Sturrock et al, 1993 Interaction of PR3 with SLPI investigated Rao et al, 1993Rao et al, 1995 Bimodal distribution of PR3 on resting neutrophil surface observed Halbwachs-Mecarelli et al, 1995 Recombinant production of PR3 in human mast cell line-1 cells as active enzyme performed Specks et al, 1996 Crystal structure of PR3 identified Fujinaga et al, 1996 Allosteric modulation of PR3 activity by C-ANCA reported Hinkofer et al, 2015 Endothelial cytoskeletal target substrates of PR3 identified Jerke et al, 2015 Inhibitors and Antibodies Targeting PR3 605 than HNE (Korkmaz et al, 2005a(Korkmaz et al, , 2013aSinden et al, 2015). Moreover, PR3 m was shown to inhibit the phagocytosis of apoptotic neutrophils by binding to calreticulin on apoptotic neutrophils (Gabillet et al, 2012).…”
mentioning
confidence: 99%
See 3 more Smart Citations